When Learning Disturbs Memory – Temporal Profile of Retroactive Interference of Learning on Memory Formation - Sosic-Vasic, Zrinka; Hille, Katrin; Kröner, Julia; Spitzer, Manfred; Kornmeier, Jürgen (Frontiers in Psychology, 2018)
Introduction: Consolidation is defined as the time necessary for memory stabilization after learning. In the present study we focused on effects of interference during the first twelve consolidation minutes after learning. Participants had to learn a set of German – Japanese word pairs in an initial learning task and a different set of German – Japanese word pairs in a subsequent interference task. The interference task started in different experimental conditions at different time points (0, 3, 6, and 9 minutes) after the learning task and was followed by subsequent cued recall tests. In a control experiment the interference periods were replaced by rest periods without any interference. Results: The interference task decreased memory performance by up to 20%, with negative effects at all interference time points and large variability between participants concerning both the time point and the size of maximal interference. Further, fast learners seem to be more affected by interference than slow learners. Discussion: Our results indicate that the first 12 minutes after learning are highly important for memory consolidation, without a general pattern concerning the precise time point of maximal interference across individuals. This finding raises doubts about the generalized learning recipes and calls for individuality of learning schedules.